FINANCIAL AND ECONOMIC MECHANISM OF PUBLIC ADMINISTRATION IN THE CONTEXT OF DIGITAL TRANSFORMATION OF PUBLIC SERVICES - Natalia Dragomyretska; Iryna Matvieienko; Yuliia Britsyna; Kateryna Rovynska; Iolita Adamska (Financial and credit activity problems of theory and practice, 2026)
The article is devoted to the substantiation of the financial and economic mechanism of public administration that can link budget resources with the actual effectiveness of the digital transformation of public services. The relevance of the study is determined by the fact that an increase in spending on general government services does not in itself guarantee accessibility, transparency, interoperability, and convenience of electronic interaction between citizens and enterprises with government authorities. The aim of this article is to theoretically substantiate the structure and instruments of the financial and economic mechanism for public administration of the digital transformation of public services and to assess the alignment of the budget burden with the results of digital public service delivery in a sample of European Union countries. The information base consists of Eurostat data on general government expenditure for 2023 and the results of the eGovernment Benchmark 2026 obtained from the assessment of public services. The sample covers 12 countries of the European Union, namely Austria, Bulgaria, Croatia, Latvia, Lithuania, Poland, Romania, Slovakia, and Slovenia. The proposed methodology combines Saaty hierarchy analysis, entropy determination of objective weights, TOPSIS method, input-oriented DEA-BCC model, synergistic aggregation of results, standardized regression testing and scenario modeling. A system of 8 criteria has been formed, covering fiscal resource intensity, administrative and debt costs, the level of digitalization of services, transparency, interoperability, user support, and the basic quality of government portals. The most hybrid scales received basic portal quality, transparency, and interoperability. According to the synergy index, Estonia, Austria and Lithuania took the highest positions, while Hungary and Romania received the lowest results. The regression test showed the statistically significant impact of interoperability on the overall assessment of public services. The target scenario of resource redistribution and increased digital maturity increases the overall result, while the stress scenario reduces it. The practical significance of the results lies in the formation of tools for program-targeted budgeting, performance-based financing, management of the full cost of public services, and prioritization of investments in general digital infrastructure.